O mercado brasileiro de diesel, gasolina e GLP entre 2000 e 2019 - caracterização histórica e panorama atual - Otávio Grassi Gonçalves (2020)
The consumption of petroleum will still follow high for many years, even though it's share on the global energetic matrix comes decreasing year by year. In Brazil, even with a greener energetic matrix if compared to the global average, it won't be different. The oil products, mainly diesel, gasoline and LPG, has a key role on economy and on Brazilian’s lives. The prices variations of these oil products have a straight impact on the economic activity and the consumption pattern. From this dependence, Petrobras, statal company stablished with the goal to guarantee the Brazilian access of these and others fuels, has a central function on the oil products productive chain, controlling more than 98% of Brazilian’s capacity of oil processing. The decisions taken by the company and the changes on relevant legislation, impact the exploration and production of oil, the usage factor of the national refining park, the exports and imports of oil products and the final price to consumer. In that context, this dissertation aims to characterize the Brazilian fuel market as from a historical bibliographic research, going through legislation changes and analyses the current scenario, based on official data from various actors of the Brazilian and international oil sector. Since 2000, the country has significantly increased crude oil exports, while decreased imports, especially after the pre-salt production began. On the same period, oil products consumption also increased, but that wasn't totally attended by the national refining park. From 2016, Petrobras started to adjust more often oil products prices on the refineries, raising domestic prices and making possible the imports of oil products by third parties to resail on domestic market. As consequence, the national refineries started to operate with great idleness, raising the external dependence. In 2019, the external dependence of diesel gets around 24.1%, LPG around 26.7% while gasoline gets around 10.3%, given that Brazil was an exporter of that fuel by 2010. Analyzing the origin of those imports, we notice a strong presence of USA fuels in the Brazilian market, by having significantly increase its exports to Brazil from 2016. The reduction of Brazilian’s refineries idleness could reduce the volume and the expenditure with fuel imports. Moreover, it's important to highlight that the fuel prices increasing, impact more the population’s most poor group.